(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
It is known that philosophy has always tried to find ways to solve the current problems of its time. By the 20th century, humanity has achieved great achievements in the field of science and technology development. But at the same time, this century was also a period of social upheavals, two world wars, ecological crisis, and heavy losses. This was reflected in the development of philosophical thought; it clearly determined the importance and scope of the problems that various directions and currents were engaged in. As a result of this, in the philosophy of the present era, there are finally different currents and trends. In turn, this determines the main features of science and practice and the development of the science of philosophy in the second half of the 19th century and until now.